Acute effect of a continuous running exercise on memory in University students. Urban environment vs. Natural environment - Morente-Oria, Honorato Fernando; González Fernández, Francisco Tomás; Ramos Pérez, Daniel; Baena Morales, Salvador (My University, 2020)
The associated benefits of physical exercise on cognition have been studied in terms of different variables. These benefits in natural environments have been studied during the last decades, and several investigations have shown contradictory results, it could be explained by the diversity of methodological variables that influence the results. The present study aims to analyze the acute effect of a 10 km resistance test in two environments (natural and artificial) on working memory, evaluated with the Digit Span Test. Thirteen highly trained University Students exceeded the inclusion criteria for the study, the methodological recommendations found in previous studies were implemented. The physical exercise intervention was running 10 kilometers at a rate of between 4.00 min/km and 4.10 min/km. This exercise was done in two circuits, in an artificial and natural environment. The subjective perception of effort and the control over the difficulty of the two circuits were controlled to confirm the same level of intensity. One-way ANOVA with Pre-Artificial Environment Condition (0.23 ± 0.16) and Post Artificial Environment Condition (0.94 ± 0.03)] revealed a significant main effect of environment condition, t (13) = 2.14, p < .05, d = 0.62. The results obtained showed how the natural environment produced significant improvements however, the artificial environment improved the results in the cognitive test, although not significantly. The results could be explained by the theory of restoration of attention that natural environments represent, confirming the hypothesis that the performance of physical exercise in natural environments produces an additional effect on working memory
Keywords: Educación física; Estudiantes universitarios; Memoria; Aptitudes de aprendizaje; Naturaleza; Ciudades; Ejercicio físico; Training; Memory; Natural environment; Urban environment